PERTSEVITE, A NEW SILICATIAN MAGNESIOBORATE MINERAL WITH AN END-MEMBER COMPOSITION MG2BO3F, IN KOTOITE MARBLE FROM EAST OF VERKHOYANSK, SAKHA-YAKUTIA, RUSSIA - Schreyer W.; Bernhardt H.; Medenbach O.; Armbruster T. (My University, 2003)
Pertsevite is a new Mg borate from a contact-metasomatic kotoite marble from the region east of Verkhoyansk, Sakha-Yakutia, northeastern Siberia. The end member is defined as Mg2BO3F, which is the composition of a synthetic phase. The natural material consistently contains from 4 to 12 wt.% SiO2 as well as some OH. This is due to the substitutions Si + 0 for B + F and OH for F. A representative composition, which is an intermediate member of a solid solution series Mg2BO3(FOH) - Mg2SiO4, has the composition (EMP data, OH calculated for charge balance) SiO2 8.25; Al2O3 0. 10; B2O3 22.44; FeO 3.71; MnO 0.65; MgO 57.39; CaO 0.24; F 7.29; H2Ocalc, 1.67; total 98.97 wt.%, corresponding to (Mg1.88Fe0.072+Mn0.01)(B0.85Si0.18)O3.21F0.54(OH)(0.24) or simply Mg-2(B0.8Si0.2)O-3.2(F,OH)(0.8). A general formula of silicatian pertsevite may be given as Mg-2(B,Si)O-3(F,OH,O). Like the synthetic end member Mg2BO3F, silicatian pertsevite is orthorhombic, space group Pna2(1), with a = 20.490(6), b = 4.571 (1), c = 11.890(3) Angstrom, V = 1113.61(5) Angstrom(3), Z = 16 and D-calc = 3.12 g/cm(3) for the above composition. Its structure is based on a hexagonal close-packed arrangement of anions similarly as for forsterite, but with cations occupying different sets of voids. BO3 triangles are randomly replaced by SiO4 tetrahedra with Si lying outside of the planes defined by the BO3 triangles. The crystals are colorless in thin section, biaxial (+) with (for the above composition) alpha = 1.609(l), beta = 1.620(l), gamma = 1.642(l) for 589 nm, 2V(Zmeas) = 65(1)degrees and no visible dispersion. In the one thin section of the kotoite marble available, pertsevite occurs as anhedral crystals interspersed with calcite, kotoite, forsterite, clinohumite, spinel, ludwigite and a new member of the hulsite group. Based on analytical data, but also on structural considerations, there is a large miscibility gap between silicatian pertsevite and practically boron-free forsterite. Pertsevite is probably more widespread than this single example suggests; its being overlooked may be explained by its close resemblance to forsterite and humite group minerals in thin section.
Keywords: Pertsevite